Checklist of eels of Taiwan (orders Anguilliformes and Saccopharyngiformes): An update - Ho, Hsuan-Ching; Smith, David G.; Tighe, Kenneth A.; Hibino, Yusuke; Mccosker, John E. (Zootaxa, 2018)
The eel fauna (orders Anguilliformes and Saccopharyngiformes) of Taiwan is increased to 14 families, 79 genera and 232 species. Previous studies (Ho et al., 2015b, c) showed Taiwan had the highest diversity of eels in the world: this is further supported in the present updated work. Elsewhere in this volume, 16 species are newly described and 13 species are newly added to the Taiwanese ichthyofauna, mainly in the families Congridae and Synaphobranchidae. In addition, one new genus and four new species are described from adjacent waters in the Pacific Ocean. A total of 58 new species of the two eel orders are described from Taiwan; 52 of them are valid, and 37 are only found in Taiwan. Four names previously recorded in Taiwan are described as new in present special issue and are removed from the fauna of Taiwan accordingly. This work provides a foundation for the study of eel diversity in Taiwan.